1998
DOI: 10.1046/j.1523-1755.1998.00879.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thyroid hormone on the neonatal renal cortical Na+/H+ antiporter

Abstract: The neonatal proximal tubule has a lower rate of bicarbonate absorption than that of adults. This is due, in part, to a lower rate of apical membrane Na+/H+ antiporter activity. The purpose of these studies was to examine if thyroid hormone could be a factor in the maturational increase in Na+/H+ antiporter activity. Hypothyroid (0.01% propylthiouracil in drinking water starting at day 14 gestation and throughout the postnatal period), euthyroid, and hyperthyroid (intraperitoneal triiodothyronine, 10 microgram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
82
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(96 citation statements)
references
References 36 publications
12
82
2
Order By: Relevance
“…The cortex was dissected and then homogenized with 20 strokes with a polytetrafluoroethylene-glass homogenizer at 4°C. BBMV were then isolated by differential centrifugation and magnesium precipitation as previously described (21). The final BBMV fraction was resuspended in isolation buffer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cortex was dissected and then homogenized with 20 strokes with a polytetrafluoroethylene-glass homogenizer at 4°C. BBMV were then isolated by differential centrifugation and magnesium precipitation as previously described (21). The final BBMV fraction was resuspended in isolation buffer.…”
Section: Methodsmentioning
confidence: 99%
“…BBMV protein (50 g/ lane) was denatured and separated on a 7.5% polyacrylamide gel as previously described (21,22). The proteins were transferred to polyvinylidene difluoride membrane overnight at 140 mA at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…However, there are anecdotal reports that long-term use of angiotensin converting enzyme (ACE) inhibitors or AT II receptor blockers (ARBs) did not regress renal hypertrophy in hyperthyroid animals (31,32). Thyroid hormone participates in the development of many co-transport systems in the renal tubule including renal Na + co-transported phosphate, cortical Na + /H + exchanger (NHE), and Na + -K + adenosine-triphosphatase (33)(34)(35)(36)(37). Notably, Wijkhuisen et al (38) suggested that thyroid hormone regulates the development of several energy metabolism enzymes of proximal convoluted tubule of perinatal rats such us the enzyme 3-ketoacidCoA transferase, citrate synthase and carnitine acetyltransferase.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, thyroid hormones are raised in cold-exposed mothers (Symonds et al 1988a) and decrease with parity (Tasende et al 2002), differences that are maintained through lactation (Symonds et al 1990). Hypothyroidism has been shown to delay kidney maturation after birth, resulting in decreased renal cortical Na C /H C transporter activity and brush border membrane NHE-3 protein abundance (Baum et al 1998), blunted maturational increase in both Na C /H C and Cl K /OH K exchange activity (Shah et al 2000), and lower rates of sodiumdependent proton secretion (Gupta et al 2004). Differences in maternal and neonatal plasma thyroid hormone concentrations may, therefore, contribute to the maternal effects on mitochondrial protein abundance in the kidney we have found that appear to be confined to the tubular region.…”
Section: The Kidneymentioning
confidence: 99%